Pengenalan Isu Keuangan Kontemporer dan Penulisan Ilmiah bagi Mahasiswa Program Studi Manajemen - Saputra, Sahdan; Elthia, Memy Wardani; Ihyani, Layali (CV. Global Cendekia Inti, 2025)
The rapid development of the financial sector has given rise to strategic issues such as fintech, crypto assets, green finance, ESG, and the impact of global trade wars, which require serious attention from academics, particularly students in economics and management. However, many students still face difficulties in formulating relevant research titles and writing scientific articles in accordance with academic standards. This community service activity aims to enhance the capacity of Management Study Program students at Universitas Bumigora in understanding contemporary financial issues and integrating them into academic writing. The activity was conducted using a Participatory Action Research (PAR) approach through three stages: preparation, training implementation, and post-training. A total of 30 students participated in the training, which covered the introduction of financial issues, techniques for formulating research titles, and scientific writing practice. The results of the activity show an improvement in students' understanding of modern financial topics and their ability to formulate research titles and write more systematic academic paragraphs. This program is expected to encourage students to produce more relevant, high-quality, and contextually appropriate scientific work in response to current developments.